2010
DOI: 10.1111/j.1468-8123.2010.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Radon in the investigations of geo‐hazards in Polish collieries

Abstract: Outbursts (releases of gas and coal from exposed coal face) are dangerous events in coal mines, potentially leading to damage in the galleries and casualties among miners. For that reason, monitoring of this hazard is very important in collieries with seams prone to outbursts. Current hazard indicators are not sufficient for the proper prediction of geodynamic events and any effort to find a new and better method of monitoring is thus desirable. During the 1980s and 1990s, attempts were undertaken to apply spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…underground hard coal and copper mines in southern and south-western Poland (the Upper Silesian foredeep and the Sudetes) are also interesting. The values measured in hard coal mines oscillate in the range from tens to 150, 000 Bq/m 3 [37,55]. At the same time, 222 Rn activity concentration in salt caverns in copper mines, at the depth of about 1000 m b.s.l., range from 12 to 49 Bq/m 3 [38].…”
Section: Underground Minesmentioning
confidence: 93%
See 2 more Smart Citations
“…underground hard coal and copper mines in southern and south-western Poland (the Upper Silesian foredeep and the Sudetes) are also interesting. The values measured in hard coal mines oscillate in the range from tens to 150, 000 Bq/m 3 [37,55]. At the same time, 222 Rn activity concentration in salt caverns in copper mines, at the depth of about 1000 m b.s.l., range from 12 to 49 Bq/m 3 [38].…”
Section: Underground Minesmentioning
confidence: 93%
“…Measurements of 222 Rn activity concentration in the atmospheric air, soil air, the air of buildings, caves and other underground tourist sites as well as working underground mines are also performed with the use of devices that are well known in the world and have been tested in various conditions. These are, first of all, Alpha GUARD and RAD7, but also scintillation chambers, Lucas cells and semiconductor detectors used in all Poland-made devices such as different series of mining radiometers RGR [33][34][35][36][37][38]. Besides, new appliances dedicated to measuring 222 Rn activity concentration in different environments are also being developed in Poland.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Coal and gas outburst prediction. Wysocka (2010) started observations of changes of radon concentration in gas, sampled from headings, driven in endangered coal seams. Then, he reported that there is a degree of correlation between the temporal and spatial variations of radon level and the hazard level of an outburst, and it is possible to develop a "radon outburst's indicator" to support other methods of prediction of very dangerous geodynamic phenomena.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Mining water contaminated with harmful elements may also penetrate ground waters [16][17][18][19][20]. in her work, Wysocka described the problem of radon emissions following underground coal mine closures and the harmful impact of such emissions on residents [21]. Mine closure by flooding also results in additional significant changes to the stress and deformation of the rock mass, manifesting on the surface as continuous [6,22,23] and discontinuous [24] deformations, and may also be observed as mining damage [4,23,25].…”
Section: Introductionmentioning
confidence: 99%